Well met! : friends and travelling companions of Rev. Thomas Bowles : journals of travels in Egypt, Petra and the Near East, 1854 - Kennedy, D. L., 1948- (Archaeological lives., 2023)
This volume follows Rev. Thomas Bowles on his travels from Sri Lanka to Egypt and the Levant. His travel journals record the places seen and the often harsh travel conditions. Bowles' notes are amplified by chapters offering additional context and biographies for the broad cross-section of fascinating people encountered along the way.